Factors Influencing Consumers' Purchase Intention To Use Battery Electric Cars In Indonesia - Falisa, Camelia; Tricahyono, Dodie (Publisher Cv. Inara, 2025)
The market share of electric vehicles in terms of overall sales is still small in both developed and developing countries such as Indonesia. This study aims to determine the priority of factors that influence consumer purchase intention for battery electric cars in Indonesia by exploring public perceptions of this. This study uses quantitative research with a deductive approach and causality properties. The research population is consumers who buy and prospective buyers of battery electric cars in the DKI Jakarta area. With sample calculations using parameter 5, so that the minimum number of samples is 73 indicators X 5 = 365 respondents. The analysis technique uses SEM with the help of the AMOS program. The results of the study show that the integration of TPB, UTAUT-3, and NAM theories provides in-depth insights into consumer intentions to purchase battery electric vehicles (BEVs) in Indonesia. Positive attitudes and PBC contribute significantly to purchase intentions, at 16% and 14.8%, respectively, while subjective norms show a negative but significant influence. In the UTAUT-3 model, social influence and facilitating conditions contribute significantly, at 33.6% and 44.3%, respectively, emphasizing the importance of social support and infrastructure. Price value also contributes significantly at 33.2%, indicating that the perception of the economic value of electric vehicles greatly influences purchasing decisions, but other factors are not significant. Although awareness of consequences and ascription of responsibility in the NAM model have a positive effect, personal norms do not show a significant influence on purchase intentions. The implication of these findings is that to increase purchase intentions for electric vehicles, a marketing strategy is needed that includes education about the benefits, strengthening social norms, and improving infrastructure, as well as creating awareness of the economic and environmental value of electric vehicles.